1978
DOI: 10.1007/bf00447162
|View full text |Cite
|
Sign up to set email alerts
|

Die Porphyrinproduktion des Propionibacterium acnes bei Acne und Seborrhoe

Abstract: The porphyrin productions of P a.-strains, isolated on the one hand from inlfammatory acne lesions, on the other hand from sebaceous follicle filaments from 10 persons each were compared quantitatively and qualitatively, after the appropriate material had been pooled, With respect to the acne strains one could observe a somewhat increased porphyrin production as well as the discharging of a precentually greater portion of porphyrins to the surrounding material. When separated by TLC the acne material showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…HPLC analysis of acne extractions revealed a qualitatively uniform porphyrin profile, with coproporphyrin III as the major porphyrin fraction, whereas coproporphyrin I was present in low concentrations, and protoporphyrin hardly at all. This result matches the porphyrin formation of previously published in vivo (12,21,22) and in vitro studies (23)(24)(25).…”
Section: Dtscussionsupporting
confidence: 94%
See 1 more Smart Citation
“…HPLC analysis of acne extractions revealed a qualitatively uniform porphyrin profile, with coproporphyrin III as the major porphyrin fraction, whereas coproporphyrin I was present in low concentrations, and protoporphyrin hardly at all. This result matches the porphyrin formation of previously published in vivo (12,21,22) and in vitro studies (23)(24)(25).…”
Section: Dtscussionsupporting
confidence: 94%
“…The considerable inter-individual variations in the porphyrin concentration observed in the present study have also been seen in previous investigations (21,23,24). Similar porphyrin patterns in comedones and inflamtnatory acne lesions implicate that inflammation is not caused by modulation of the porphyrin profile.…”
Section: Dtscussionsupporting
confidence: 72%
“…Molecules secreted by P. acnes , such as proteases, lipases, hemolysins, and porphyrins, can degrade host tissue and have been suggested as causal factors in acne ( 16 20 ). Porphyrins can generate reactive oxygen species and induce inflammation in keratinocytes ( 21 23 ). Previous studies have shown correlations between acne severity and the concentrations of bacterium-derived porphyrins in the hair follicle.…”
Section: Introductionmentioning
confidence: 99%
“… 4,5 , 8 The release of cytokines after contact with P. acnes may be important for the attraction and migration of effector cells (lymphocytes, macrophages, neutrophils) into the epithelial tissue. One possible mechanism for keratinocyte damage leading to cytokine release may be the production and secretion of porphyrins by P. acnes 9 . We analysed by high‐performance liquid chromatography (HPLC) the in vivo porphyrin pattern produced by P. acnes which had been obtained from inflammatory acne lesions.…”
mentioning
confidence: 99%